Peran Ekonomi Kreatif di Bidang Kuliner Khas Provinsi Jambi Pada Masa Pandemi Covid-19 - Khuswatun Hasanah; Dilla Dwi RR (Journal of Applied Accounting and Business, 2022)
The Covid-19 outbreak that attacks all corners of the world certainly has various impacts, both positive and negative. Various sectors experienced losses, even to the point of closing, but on the other hand there were positive impacts that were seen, namely the number of businesses carried out, especially the younger generation who started their businesses from home during the lockdown period. This research was conducted from January 2021 to December 2021 by collecting primary and secondary data through interviews and distributing questionnaires. In the future, the results of this study can be used as a basis for further researchers in conducting similar research and providing knowledge and understanding of entrepreneurship to readers.